2015
DOI: 10.2147/jpr.s86732
|View full text |Cite
|
Sign up to set email alerts
|

The influence of repeated pain stimulation on the emotional aspect of pain: a preliminary study in healthy volunteers

Abstract: PurposePain is a multidimensional experience with sensory-discriminative, cognitive-evaluative, and affective-motivational components. Emotional factors, such as unpleasantness or anxiety, are known to have influence on pain in humans. Repeated painful stimulation has been reported to reduce subjective pain intensity. Nevertheless, there is little evidence of the influence of such stimulation on the emotional factors of pain. The aim of this study was to evaluate the influence of repeated painful stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The result that participating athletes did not show any significant changes in pain ratings over the season (according to VAS) accords with other research that has found that pain perception does not necessarily change as a result of repeated exposure to pain [38].…”
Section: Pain Tolerancesupporting
confidence: 89%
“…The result that participating athletes did not show any significant changes in pain ratings over the season (according to VAS) accords with other research that has found that pain perception does not necessarily change as a result of repeated exposure to pain [38].…”
Section: Pain Tolerancesupporting
confidence: 89%
“…1 ). This mechanism could be evolutionarily developed to restore nociceptive system after habituation or adaption to current painful sensations for sensing new aversive stimuli in the future by transferring the current somatic pain experience to its non-habituated affective component 71 . Thus, although most researchers view alexithymia as a risk factor for pain, the opposite may occur—the experience of stressors, including pain, may reduce the ability to perceive, identify, and/or differentiate emotions as a protective mechanism for inhibiting attention to pain sensation or redirecting its somatic negative experience to the affective system.…”
Section: Discussionmentioning
confidence: 99%
“…Pertinently, chronic pain has been consistently associated with anxiety 103 – 105 —a behavioural outcome observed for our repeatedly injected animals. Furthermore, preclinical studies using electric foot shock paradigms, which also elicit pain, likewise report an increase in anxiety-like behaviour 106 , 107 , and clinical studies using repeated pain stimulation show that, despite pain habituation, exposed individuals report increased anxiety 108 . Interestingly, previous research shows how repeated injection differentially alters affective outcomes in rats with high and low emotionality, with low responders showing no change in depressive-like states 21 .…”
Section: Discussionmentioning
confidence: 99%